Transglutaminase 2 in breast cancer metastasis and drug resistance - Li, Mengxin; Wang, Xuanzhong; Hong, Jinghui; Mao, Juanjuan; Chen, Jiasi; Chen, Xuyang; Du, Ye; Song, Dong (Frontiers in Cell and Developmental Biology, 2024)
Transglutaminase 2 (TG2) is a widely distributed multifunctional protein with various enzymatic and non-enzymatic activities. It is becoming increasingly evident that high levels of TG2 in tumors induce the occurrence of epithelial to mesenchymal transition (EMT) and the acquisition of stem cell-like phenotypes, promoting tumor metastasis and drug resistance. By regulating intracellular and extracellular signaling pathways, TG2 promotes breast cancer metastasis to lung, brain, liver and bone, as well as resistance to various chemotherapy drugs including docetaxel, doxorubicin, platinum and neratinib. More importantly, recent studies described the involvement of TG2 in PD-1/PD-L1 inhibitors resistance. An in-depth understanding of the role that TG2 plays in the progression of metastasis and drug resistance will offer new therapeutic targets for breast cancer treatment. This review covers the extensive and rapidly growing field of the role of TG2 in breast cancer. Based on the role of TG2 in EMT, we summarize TG2-related signaling pathways in breast cancer metastasis and drug resistance and discuss TG2 as a therapeutic target.